VALORILE ESTETICE. PUTEREA EDUCATIV-FORMATIVĂ A DESIGNULUI VESTIMENTAR - USM ADMIN (Moldova State University, 2008)
This article contribute to the promotion of authentic values in training - development of creative personalities, receptive to the perception of beauty in costumes' art; proclaims the axiom of aesthetic values of the costume, of the "good taste", following the development of "fashion" phenomenon. This article touches the issue of education through costume of the learning youth in terms of aesthetic, artistic and visual. It shows the stages of learning the elements, principles and regularities / laws specific for the dress design, which can not be acquired without: • waking up interest for "aesthetic object"; • development of aesthetic taste; • stimulating the creative skills of students towards beautiful.